2017
DOI: 10.1007/s11195-017-9512-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Sexual Behavior of Teenagers and Young Adults with Cerebral Palsy: The Role of Sexual Needs and Sexual Esteem

Abstract: Sexuality is an inherent attribute of all human beings regardless of their race, religion and the level of physical fitness. The way it is perceived and manifested is determined by a number of biopsychosocial factors. In some people, including persons with cerebral palsy, the factors and their influence are rooted in the psychophysical condition of the human body. The aim of this study was to answer the question about how the levels of sexual esteem and sexual needs differentiate the sexual behaviors of young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
(45 reference statements)
1
7
0
Order By: Relevance
“…Regarding sexual behaviors, kissing, touching, and caressing, receiving stimulation of erogenous zones and performing oral sex were the most frequently reported sexual activities by participants. This finding is supported by the results of earlier studies [29][30][31], which indicated that people with physical disabilities have significantly lower odds of partaking in sexual activities that involve penetration and greater chances of not engaging in sex, at all. Nevertheless, the vast majority of those who reported not having sex stated that this was because of a lack of opportunity or lack of a partner.…”
Section: Discussionsupporting
confidence: 76%
“…Regarding sexual behaviors, kissing, touching, and caressing, receiving stimulation of erogenous zones and performing oral sex were the most frequently reported sexual activities by participants. This finding is supported by the results of earlier studies [29][30][31], which indicated that people with physical disabilities have significantly lower odds of partaking in sexual activities that involve penetration and greater chances of not engaging in sex, at all. Nevertheless, the vast majority of those who reported not having sex stated that this was because of a lack of opportunity or lack of a partner.…”
Section: Discussionsupporting
confidence: 76%
“…Sexual developments in individuals with intellectual disabilities are not much different from the sexual developments in other individuals. However, individual differences make the sexual experience and the changes occurring in this period different as well (Ariadni et al, 2017; Czapla and Otrębski, 2018; Gordon et al, 2004). Seyyar (2012) stated that most of the parents were uncomfortable with the interest in sexuality that their children with intellectual disabilities had, and felt helpless in this situation.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate sexual education programs should be prepared for the sustainability of health in adolescents with intellectual disabilities to include sex differences, knowledge of one’s body, sexual satisfaction capability, genital hygiene, the physical and physiological changes of adolescence, sexuality information, and information about sexual abuse (Bork, 2017; Isler et al, 2009; Servais, 2006). In cases where the sexual health education needed by these adolescents cannot be provided, risks including sexual abuse, sexually transmitted diseases, low self-respect, social isolation and a generally low quality of life are known to be increasing (Czapla and Otrębski, 2018; Sinclair et al, 2015; Sweeney, 2008; Taleporos and McCabe, 2005). Clatos and Asare (2016) found that a sexual education program had a positive effect on the knowledge of sexuality and on the sexual communication behavior of parents of children with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…In the H-SE&SN subgroup most respondents (nearly 60.00%) went out on dates 'sometimes' , as many as 54.50% had already been in a few (2-3) relationships, and half of them had had their sexual initiation after 20 years of age. In contrast, in the L-SN&SE subgroup, 28.20% dated 'sometimes' , almost 48.70% of respondents had never had a partner, and 71.70% had not had their sexual initiation yet [20]. This indicates that persons with disabilities as a group are very diverse and should always be treated with a personalized approach.…”
Section: Sexual Counselling and Sexual Education Of People With Disab...mentioning
confidence: 94%